Pengaruh Persepsi Dukungan Autonomy dan Dukungan Sosial Terhadap Motivasi Intrinsik Musik - Kusuma, Jennifer Aristasya; Yuliawati, Livia (Universitas Ciputra Surabaya, 2020)
Learning music through formal lessons have a lot of benefit for teenagers. Unfortunately, data shows that teenagers tend to quit music lessons because of the lack of interest and motivation. Motivation, especially intrinsic motivation is an important aspect in the continuation of having formal music lessons because it can predict a more effective music practice. Support from teacher and parents are needed in order to increase the student’s intrinsic motivation. The hypothesis is that there is a positive effect between perceived autonomy support and perceived social support towards intrinsic motivation to play music. This research uses quantitative approach with correlational design. Subjects in this research are 120 teenagers who is currently taking music lessons in Surabaya and obtained by means of accidental sampling. Data analysis shows the main hypothesis is only partially accepted, where it is found only perceived autonomy support can predict intrinsic motivation while perceived social support have no effect. Further analysis shows that perceived autonomy and social support from music teacher has a significant effect towards teenager’s intrinsic motivation. Other factors such as what age the student start having lessons also have an effect towards their intrinsic motivation as teenagers.